A New Evaluation Method to the Consistency of Lithium-Ion Batteries in Electric Vehicles - Wen Feng; Lin Cheng; Jiang Jiuchun; Wang Zhanguo (2012 Asia-Pacific Power and Energy Engineering Conference, 2012)
To resolve the problem that the terminal voltage of the battery cannot effectively reflect the internal differences between cells, four parameters including Ohmic resistance, polarization voltage, maximum available capacity and state of charge (SOC) of the battery were proposed to evaluate the consistency of the battery pack. The characteristics of each parameter during charge and discharge were theoretically analyzed and experimentally tested.